Evaluation of anatomical and functional success in canalicular laceration repair using anterior segment optical coherence tomography and dacryoscintigraphy - Çisil Erkan Pota; Özge Ekin Geçer Şerifoğlu; Aslı Çetinkaya Yaprak; Hatice Deniz İlhan; Adil Boz (Photodiagnosis and Photodynamic Therapy)
Purpose: To assess the anatomical and functional outcomes in patients who underwent surgery for canalicular laceration and did not experience significant epiphora, and to compare these outcomes with contralateral uninjured eye. Method: Dacryoscintigraphy, anterior segment optical coherence tomography (OCT), MUNK scores, and a satisfaction questionnaire were administered to 24 patients who had canalicular laceration repair without significant epiphora and had a minimum of 6 months of follow-up. Tear meniscus height (TMH), depth (TMD), and area (TMA) were measured using anterior segment OCT and compared with the values in the uninjured eye. Results: Sixteen patients (67 %) had lower, 7 (29 %) had upper canaliculus, and one (4 %) had lacerations in both canaliculi. Five patients (20.83 %) had concomitant orbital fractures, and three patients (12.5 %) underwent additional repair for corneoscleral laceration. Bicanalicular silicone tube intubation was performed in one patient, while Mini-Monoka stent intubation was used for all other patients. The mean follow-up period was 41 ± 22.3 months, and the mean interval between trauma and surgery was 30.2 ± 29 h. The mean duration until tube removal was 3 ± 2.54 months. The MUNK score was 1 in eight patients (33 %) and 0 in sixteen patients (67 %). Canalicular lacerations occurred due to home accidents in 8 patients, work accidents in 4, assaults in 5, and traffic accidents in 7.Dacryoscintigraphy showed drainage of tracer into the nasal cavity in dynamic imaging for 12 patients. Five patients had retention in the sac, four had prolonged and reduced drainage, one had reduced drainage, and two showed no drainage in the first and second hour images. In the operated eye, the mean tear meniscus height (TMH) was 279.6 µm, depth (TMD) was 215 µm, and area (TMA) was 28.9 µm². In the healthy eye, the mean TMH was 221.5 µm, TMD was 152.5 µm, and TMA was 15.3 µm². The anterior segment OCT values for the affected eye were statistically significantly higher than those for the healthy eye (p = 0.044 for TMH, p = 0.003 for TMD, p = 0.006 for TMA). TMD and TMA were statistically significantly higher in patients with a MUNK score of 1 (p = 0.019 for TMD, p = 0.05 for TMA). Abnormal dacryoscintigraphy results were more common in patients with globe injuries requiring additional surgery. Conclusion: Although patients did not report epiphora after canalicular laceration repair, our observations indicated potential functional and anatomical differences in dacryoscintigraphy and anterior segment OCT compared to their healthy eyes. We believe that close follow-up is crucial to identify and address any issues that may arise in the future following surgery.